Construction Strength Analysis of a 250-Tonne Capacity Deck Crane Barge with Longitudinal Variation - Kharis Abdullah; Sumardiono; M. Lukman Arif; Agung Prasetya Utomo; Denny Oktavina Radianto (WAVE: Jurnal Ilmiah Teknologi Maritim, 2023)
A deck crane barge is a barge with a crane system attached to the deck for loading, unloading, and lifting various materials or supporting equipment. In marine building construction, strength assessment must be carried out to ensure that the built design will not fail. The finite element method is one method to perform strength assessment of ship construction faster and simplify calculating. This study assessed the strength of crane barge decks with three variations of longitudinal size with reduced longitudinal size on the web and face plate with the element method. From the calculation results, Model A or the existing construction, has the smallest Von Mises Stress, while Model C, with reduced web and face plate size to L 80 x 80 x 8 mm, has the largest Von Mises Stress. The reduction in the size of the faceplate and web plate in the longitudinal section reduced the strength of the ship construction with higher stress values. However, all three tested Models had Von Mises Stresses below the maximum permissible stress required by BKI.